The stability improvements of dye-sensitized solar cell with natural template for photoanode using lignin extracted from rice husk - Gita Rabelsa; Shobih; Jojo Hidayat; Phutri Milana; Widhya Budiawan; Erdin Almuqqodas; Natalita M. Nursam; Ahmad Ibrahim; Lia M. Pranoto; Yuliar Firdaus; Brian Yuliarto (Heliyon)
In response to escalating global concerns over environmental pollution, the development of green dye-sensitized solar cells (DSSCs) has emerged as a promising technology for solar energy conversion. This study harnesses the potential of rice husk, an abundant agricultural waste in Indonesia, by extracting lignin through a simple recycling method. Lignin acts as a natural, non-toxic dopant and template for TiO₂ composites, enhancing the stability of the photoanode in DSSCs. A TiO₂ photoanode modified with 5 % lignin achieved a power conversion efficiency (PCE) of 4.81 %. After a 90-day stability test, the TiO2/lignin 5 % composite retained 78 % of its initial PCE, significantly outperforming pristine TiO₂ in terms of short-circuit current density (JSC) and open-circuit voltage (VOC). This improved stability is attributed to increased porosity, better lignin dispersion within the TiO₂ matrix, prevention of agglomeration, enhanced surface area for dye adsorption, and reduced electrolyte leakage. Furthermore, lignin's high thermal stability on the TiO₂ surface provides additional protection against dye degradation and electrolyte evaporation during repeated light exposure.